Sistem Informasi Pemesanan Jasa Make Up Artis (MUA) Hesti Rokah Berbasis Web - mitha triana; yulina (Riset Sinergi Indonesia (RISINDO), 2026)
Hesti Rokah is a Make Up Artist (MUA) service provider who is currently facing operational challenges due to manual reservation and scheduling. The use of short messages in the business process triggers the risk of schedule inaccuracy, difficulty in accessing portfolios for customers, and service inefficiencies. This research aims to design and build a web-based MUA service booking system to optimize business process efficiency, facilitate self-reservations for customers, and integrate portfolio data and schedule information concisely. The system development uses the Rapid Application Development (RAD) method to support rapid iteration and intensive user involvement. The system modeling is visualized using the Unified Modeling Language (UML), while its implementation is based on the PHP programming language with the CodeIgniter framework and a MySQL database. The result of this research is a MUA service booking application that involves two main actors, namely the Admin (owner) and the Customer. Key features include service package management, bold booking, payment confirmation, and real-time schedule monitoring. The existence of this system is expected to create a more structured, transparent, and accessible 24/7 booking process, thereby increasing customer satisfaction and expanding the marketing reach of MUA Hesti Rokah.